Frontiers in Electronic Technologies Trends and Challenges - Prabaharan, S.R.S; Thalmann, Nadia Magnenat; Kanchana Bhaaskaran, V. S. (Lecture Notes in Electrical Engineering, 2017)
This book is a collection of keynote lectures from international experts presented at International Conference on NextGen Electronic Technologies (ICNETS2-2016). ICNETS2 encompasses six symposia covering all aspects of electronics and communications domains, including relevant nano/micro materials and devices . This volume comprises of recent research in areas like computational signal processing analysis, intelligent embedded systems, nanoelectronic materials and devices, optical and microwave technologies, VLSI design: circuits systems and application, and wireless communication networks, and the internet of things. The contents of this book will be useful to researchers, professionals, and students working in the core areas of electronics and their applications, especially to signal processing, embedded systems, and networking.